Kajian Penggunaan Obat Off-Label Pada Penyakit ISPA Pasien Pediatri di RSUD Majene: Study of Off-Label Drugs Use in Pediatric Patients at Majene General Hospital - Nurul Syafitri AR; Muhammad Faisal; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Acute Respiratory Infection (ARI) is an infection that attacks the human respiratory tract with the highest number of sufferers being found at the age of toddlers. The limitations of the types of drugs that can be used in the age range of children aged 0-2 years cause the treatment of patients to use off-label drugs. categories of off-label age, off-label indication and off-label route of administration. This study is a descriptive type of research with data collection carried out retrospectively, there are 88 medical records of pediatric patients with a diagnosis of Pneumonia, Common Cold, Allergic Rhinitis and Asthma At Majene Hospital in the period January to December 2020. Male (55.68%) and female (44.31%) and found 26 off-label drug prescriptions, off-label drug use classified as off-label age 19, off-label indication use 5 and the use of off-label route of administration 2. The most widely prescribed type of off-label drug is Chlorpheniramine Maleate. According to the literature, the use of off-label drugs is based on a sound scientific basis with low risk. Based on the results of this study, it is known that the use of off-label drugs in children is quite high so that pharmacists need to monitor the risks related to drug use.